Exploring the effect of early menarche on sexual violence among adolescent girls and young women in southeastern Ghana: a longitudinal mediation analysis - Mobolaji Ibitoye; Marni Sommer; Leslie L. Davidson; Theo G. M. Sandfort (Sexual and Reproductive Health Matters)
Research from several high-income countries links early menarche with an increased risk for sexual violence. However, the role of early menarche in adolescent girls’ and young women’s sexual violence risk in sub-Saharan Africa, where sexual violence rates are high, is not well understood. The current study explores the association between early menarche and sexual violence in Ghana with secondary analysis of data collected from 700 adolescent girls and young women followed over three years. Logistic regressions were used to assess the cross-sectional association between early menarche and sexual violence. Generalised estimating equations were used to assess whether the association between early menarche and sexual violence persisted over time. Inverse odds weighting was used to test potential mediators of the association between early menarche and sexual violence. Sexual violence was fairly common in the study sample, with 27% reporting having experienced sexual violence at baseline, and approximately 50% at year three. Early menarche was associated with 72% greater odds of having experienced sexual violence at baseline (95% confidence interval: 1.01–2.93). However, the odds ratio attenuated and lost significance over the three-year study period, with a lower risk of sexual violence among girls with early menarche at year three. Neither child marriage nor early sexual initiation significantly mediated the association between early menarche and sexual violence. The findings suggest that early-maturing girls may be particularly vulnerable to sexual violence in early adolescence, thus necessitating prevention interventions around the time of menarche to reduce the risk for sexual violence.